2020
DOI: 10.31234/osf.io/cndz7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological responses during the COVID-19 outbreak among university students in Bangladesh

Abstract: The COVID-19 pandemic has impacted many individuals, including university students typically at a developmental stage of emerging adulthood, and facing disruptions to their education. University students may be particularly vulnerable to the mental health sequelae of the current COVID-19-related lockdown in Bangladesh. The study aimed to assess the prevalence of depression, anxiety, and stress and associated factors among university students in Bangladesh early in the COVID-19 outbreak. An internet-based surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
91
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 26 publications
20
91
1
6
Order By: Relevance
“…In the present study, anxiety and depression were significantly higher among participants who did not engage in physical exercising compared to those who did, which is similar to prior studies conducted in Bangladesh among university students [37,38]. HCWs who smoked cigarettes were more likely to be anxious and depressed than were non-smokers, which consistent with previous studies [43][44][45].…”
Section: Comparing With Other Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, anxiety and depression were significantly higher among participants who did not engage in physical exercising compared to those who did, which is similar to prior studies conducted in Bangladesh among university students [37,38]. HCWs who smoked cigarettes were more likely to be anxious and depressed than were non-smokers, which consistent with previous studies [43][44][45].…”
Section: Comparing With Other Studiessupporting
confidence: 91%
“…The extent to which the findings represent cultural differences, differences in healthcare systems, and their responses during the COVID-19 pandemic, instruments used to assess anxiety and depression or other factors warrants additional investigation. Females were more likely to experience anxiety and depression, similar to a prior study conducted in Bangladesh during the COVID-19 [37]. However, the findings contrast with those from a study among university students, showed no gender differences [38].…”
Section: Comparing With Other Studiessupporting
confidence: 71%
“…Depressive symptoms was comparatively prevalent to a lower extent (49.9%), where 26.6% of students scored 8-10, as having symptoms of mild depressive symptoms in HADS sub-scale. These findings are in line with another contemporary Bangladeshi study that found 63.6% and 62.9% of university students were anxious and having depressive symptoms respectively by using the DASS-21 questionnaire (Islam et al, 2020). Surprisingly, study findings of Islam et al, (2020) challenged our assumption of higher depression and anxiety prevalence in medical students, however, it is possible that COVID-19 may have a similar psychological impact on all university students.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in line with another contemporary Bangladeshi study that found 63.6% and 62.9% of university students were anxious and having depressive symptoms respectively by using the DASS-21 questionnaire (Islam et al, 2020). Surprisingly, study findings of Islam et al, (2020) challenged our assumption of higher depression and anxiety prevalence in medical students, however, it is possible that COVID-19 may have a similar psychological impact on all university students. Alternatively, usage of different scales while measuring anxiety and depression level may cause variance in the study findings.…”
Section: Discussionsupporting
confidence: 89%
“…This survey was conducted during a 10-day period, while the number of newly diagnosed cases was increasing in Bangladesh, and during which, substantial restrictions that included spatial distancing, home quarantine, social isolation, and travel restriction were in place. In a prior study focused on mental health conducted earlier during the outbreak in Bangladesh, we reported that 55.3% participants did not engage in physical exercise while in home quarantine, and 33.9% browsed internet more than 6 h per day [ 39 ]. We also reported that those individuals who reported vulnerable mental states (i.e., depression, anxiety, and stress) were significantly more likely not to engage in physical exercise and to browse the internet for longer periods of time.…”
Section: Discussionmentioning
confidence: 99%